Magnetic properties of EuFe0.5Mn0.5O3 complex perovskite - Silva-Santana M.C. (2020)
In this study, we determined the crystallographic, magnetization and electrical resistivity properties of a EuFe0.5Mn0.5O3 complex perovskite produced using a combustion synthesis method. The sample crystallized as an orthorhombic perovskite belonging to the Pbnm space group. Magnetization measurements indicated spin reorientation at 206 K and weak ferromagnetic-like ordering at low temperatures. Determining the magnetization as a function of the magnetic field demonstrated the presence of magnetic order, even at room temperature. Resistivity measurements indicated the existence of a small polaron conduction mechanism at high temperature. © 2020